Insights on the Early Pleistocene Hominin Population of the Guadix-Baza Depression (SE Spain) and a Review on the Ecology of the First Peopling of Europe - Palmqvist, Paul; Rodríguez-Gómez, Guillermo; Bermúdez de Castro, José María; García-Aguilar, José Manuel; Espigares, M. Patrocinio; Figueirido, Borja; Ros-Montoya, Sergio; Granados, Alejandro; Serrano, Francisco J.; Martínez-Navarro, Bienvenido; Guerra-Merchán, Antonio (Frontiers in Ecology and Evolution, 2022)
The chronology and environmental context of the first hominin dispersal in Europe have been subject to debate and controversy. The oldest settlements in Eurasia (e.g., Dmanisi, ~1.8 Ma) suggest a scenario in which the Caucasus and southern Asia were occupied ~0.4 Ma before the first peopling of Europe. Barranco León (BL) and Fuente Nueva 3 (FN3), two Early Pleistocene archaeological localities dated to ~1.4 Ma in Orce (Guadix-Baza Depression, SE Spain), provide the oldest evidence of hominin presence in Western Europe. At these sites, huge assemblages of large mammals with evidence of butchery and marrow processing have been unearthed associated to abundant Oldowan tools and a deciduous tooth of Homo sp. in the case of BL. Here, we: (i) review the Early Pleistocene archaeological sites of Europe; (ii) discuss on the subsistence strategies of these hominins, including new estimates of resource abundance for the populations of Atapuerca and Orce; (iii) use cartographic data of the sedimentary deposits for reconstructing the landscape habitable in Guadix-Baza; and (iv) calculate the size of the hominin population using an estimate of population density based on resource abundance. Our results indicate that Guadix-Baza could be home for a small hominin population of 350-280 individuals. This basin is surrounded by the highest mountainous reliefs of the Alpine-Betic orogen and shows a limited number of connecting corridors with the surrounding areas, which could have limited gene flow with other hominin populations. Isolation would eventually lead to bottlenecks, genetic drift and inbreeding depression, conditions documented in the wild dog population of the basin, which probably compromised the viability of the hominin population in the medium to long term. This explains the discontinuous nature of the archaeological record in Guadix-Baza, a situation that can also be extrapolated to the scarcity of hominin settlements for these ancient chronologies in Europe.